The Molecular Epidemiology of Resistance to Antibiotics among Klebsiella pneumoniae Isolates in Azerbaijan, Iran. (14th July 2021) - Kashefieh, Mehdi; Hosainzadegan, Hassan; Baghbanijavid, Shabnam; Ghotaslou, Reza
Abstract : Introduction . Klebsiella pneumoniae ( K. pneumoniae ) is one of the leading causes of hospital-acquired and community-acquired infections in the world. This study was conducted to investigate the molecular epidemiology of drug resistance in clinical isolates of K. pneumoniae in Azerbaijan, Iran. Materials and Methods . A total of 100 nonduplicated isolates were obtained from the different wards of Azerbaijan state hospitals, Iran, from 2019 to 2020. Antibiotic susceptibility testing was done. The DNA was extracted, and the PCR for evaluation of the resistance genes was carried out. Results . The highest antibiotic resistance was shown to ampicillin (96%), and the highest susceptibility was shown to tigecycline (9%), and 85% of isolates were multidrug resistant. The most frequent ESBL gene in the tested isolates was bla SHV-1 in 58%, followed by bla CTXM-15 (55%) and bla SHV-11 ( 42%). The qepA, oqxB, and oqxA genes were found to be 95%, 87.5%, and 70%, respectively. We detected tetB in 42%, tetA in 32%, tetD in 21%, and tetC in 16%. Seventy isolates were resistant to co-trimoxazole, and the rate of resistance genes was sul 1 in 71%, followed by sul 2 (43%), dfr ( 29%), and sul 3 (7%). The most common aminoglycoside resistance genes were ant 3 Ia, aac 6 Ib, aph 3 Ib, and APHs in 44%, 32%, 32%, and 31.4%, respectively. The most frequent resistance gene to fosfomycin was fosA (40%) and fosX (40%) followed by fosC (20%). Conclusion . The results of this study indicate the high frequency of drug resistance among K. pneumoniae isolated from hospitals of Azerbaijan state. The present study shows the presence of high levels of drug-resistant genes in various antibiotics, which are usually used in the treatment of infections due to K. pneumoniae .